Updated and revised neutron reaction data for 237Np - Chen Guochang; Wang Jimin; Cao Wentian; Tang Guoyou; Yu Baosheng (EPJ Web of Conferences, 2017)
Nuclear data with high accuracy for minor actinides play an important role in nuclear technology applications, including reactor design and operation, fuel cycle, estimation of the amount of minor actinides in high burn-up reactors and the minor actinides transmutation. Based on the evaluated experimental data, the updated and revised evaluation of a full set of n+237Np nuclear data from 10−5 eV ∼ 20 MeV are carried out and recommended. Mainly revised quantities are neutron multiplicities from fission reaction, inelastic, fission, (n, 2n) and (n, γ) reaction cross sections as well as angular distribution and so on. The promising results are obtained when the renewal evaluated data of 237Np will be used to instead of the evaluated data in CENDL-3.1 database.